Biographical Sketch of Dr. Víctor Ml. Sánchez Corrales - Leoni de León, Jorge Antonio (2014)
The academic activity given by Dr. Víctor Ml. Sánchez Corrales encompasses all possible aspects for someone committed with the aims of Higher Education and its role in society. Accomplished professor and researcher in all the axes of university duties, he also carried out a large number of functions in the university administration. It is necessary to highlight his work as a Member and Director of the University Council of the University of Costa Rica, where his vision about the university’s social, scientific, and educational roles left a remarkable impression for present and future generations.